Building stone decay : from diagnosis to conservation - Přykryl, R.; Smith, Bernard J. (Geological Society, 2007)
Stone buildings and monuments form the cultural centres of many of the world's urban areas. Frequently these areas are prone to high levels of atmospheric pollution that promote a variety of aggressive stone decay processes. Because of this, stone decay is now widely recognised as a severe threat to much of our cultural heritage. An interdisciplinary approach between geologists, environmental scientists, chemists, material scientists, civil engineers, restorers and architects aims to strengthen the knowledge base dealing with the causes, consequences, prevention and solution of stone decay problems.
"Most of the papers contained in this volume were presented during the European Geosciences Union General Assembly ('Volcanology, Geochemistry, Mineralogy 25' special session) held in Vienna (Austria) on 25-29 April 2005. In addition to these there are a number of invited contributions chosen to fill gaps in the coverage of the meeting's original aims."--Preface
Keywords: Building stones -- Biodegradation -- Congresses.; Building stones -- Deterioration -- Congresses.; Stone buildings -- Conservation and restoration -- Congresses.; Earth sciences -- Congresses.; Building, Stone -- Congresses.; Volcanological research -- Congresses.; elektronické knihy; electronic books